PENGGABUNGAN DUA KONEKSI INTERNET SERVICE PROVIDER DENGAN TEKNIK LOAD BALANCING MENGGUNAKAN METODE EQUAL COST MULTI PATH (ECMP) - Rico Andrian; Malik Abdul Azis; Muhammad Iqbal (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Computer networks are considered a primary need in the globalization era. Computer networks often used simultaneously at some specific times, leading to a bandwidth overload on the computer network. Overloaded bandwidth can cause disturbances, such as a slower network connection. This study discusses a merge of two internet service providers connections by applying a load balancing technique, namely the equal-cost multipath method. Several stages carried out in this study, including analysis, design, simulation or prototyping, implementation, monitoring, and management. This study successfully shows that an increase in the QoS value can be seen from the test parameters performed. The average throughput and jitter on all computers have increased by 0.17% and 0.68 milliseconds. The average delay for all computers has decreased by 0.9 milliseconds, whereas the average packet loss in all computers experienced a 0.58% quality improvement. Web configurations have been conducted to make the study more manageable.